2022
DOI: 10.3389/fmed.2021.792581
|View full text |Cite
|
Sign up to set email alerts
|

Single-Photon Emission Computed Tomography/Computed Tomography Image-Based Radiomics for Discriminating Vertebral Bone Metastases From Benign Bone Lesions in Patients With Tumors

Abstract: Purpose: The purpose of this study was to investigate the feasibility of Single-Photon Emission Computed Tomography/Computed Tomography (SPECT/CT) image-based radiomics in differentiating bone metastases from benign bone lesions in patients with tumors.Methods: A total of 192 lesions from 132 patients (134 in the training group, 58 in the validation group) diagnosed with vertebral bone metastases or benign bone lesions were enrolled. All images were evaluated and diagnosed independently by two physicians with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 38 publications
(37 reference statements)
0
6
0
Order By: Relevance
“…Also, there are a few studies based on SPECT/ CT-based radiomics in relation to bone diseases. Jin [14] discovered that radiomics derived from SPECT/CT images are capable of efficiently differentiating between benign bone lesions and bone metastases. This technique could be a new noninvasive alternative to assist in avoiding needless diagnostic delays.…”
Section: Differential Diagnosis Of Bone Tumorsmentioning
confidence: 99%
See 1 more Smart Citation
“…Also, there are a few studies based on SPECT/ CT-based radiomics in relation to bone diseases. Jin [14] discovered that radiomics derived from SPECT/CT images are capable of efficiently differentiating between benign bone lesions and bone metastases. This technique could be a new noninvasive alternative to assist in avoiding needless diagnostic delays.…”
Section: Differential Diagnosis Of Bone Tumorsmentioning
confidence: 99%
“…As for adults, Corino et al [39] found comparable findings. Yin et al [6] 2019 Retrospective Chordoma & Giant cell tumor CT 95 AUC = 0.79 Tagliafico et al [7] 2021 Retrospective Multiple myeloma CT 70 AUC = 0.79 Nie et al [8] 2023 Retrospective Chordoma & Giant cell tumor CT 111 AUC = 0.980 Li et al [10] 2019 Retrospective Chordoma & Chondrosarcoma MR 210 AUC = 0.87 Dai et al [11] 2020 Retrospective Osteosarcoma & Ewing sarcoma MR 66 AUC = 0.77-0.88 Mannam et al [12] 2023 Retrospective Skeletal metastases & Multiple myeloma PET/CT 40 AUC = 0.945 AUC = 0.9538 Jin et al [13] 2022 Retrospective Spine multiple myeloma & Bone metastasis PET/CT 131 AUC = 0.973 Jin et al [14] 2021 Retrospective Bone metastases & Benign bone lesions SPECT/CT 132 AUC = 0.951…”
Section: Grading Of Bone and Soft Tissue Tumorsmentioning
confidence: 99%
“…AI has also enabled the construction of predictive radiomics models for a multitude of MSK applications. Differentiation between benign and malignant osseous [19][20][21] and soft tissue lesions 21 has been performed with the use of radiomics data based on computed tomography (CT), MRI, and nuclear imaging, 22 used to build high accuracy machine learning models. Such models (with or without the addition of radiomics) have also been used to diagnose osteoarthritis [23][24][25][26] and osteoporosis 27 and to identify factors responsible for the development of early-onset osteoarthritis.…”
Section: Current Research Landscape In Msk Radiologymentioning
confidence: 99%
“…Radiomics models derived from SPECT/CT images can effectively discriminate between vertebral bone metastases and benign bone disease [15] . Unfortunately, only a few studies have used SPECT/CT radiomics to study bone metastases associated with PCa.…”
Section: Introductionmentioning
confidence: 99%